The eurocentric conception of world politics: western international theory 1760-2010 - Malafaia, Thiago Corrêa (Sociedade e Cultura, 2015)
HOBSON, John M. The eurocentric conception of world politics: western international theory 1760-2010. New York: Cambridge University Press, 2012. 392p.